God is not great : how religion poisons everything - Hitchens, Christopher (New York : Twelve, 2007)
"A case against religion and a description of the ways in which religion is man-made"--Provided by the publisher.
Putting it mildly -- Religion kills -- A short digression on the pig, or, Why Heaven hates ham -- A note on health, to which religion can be hazardous -- The metaphysical claims of religion are false -- Arguments from design -- Revelation : the nightmare of the Old Testament -- The New Testament exceeds the evil of the Old one -- The Koran is borrowed from both Jewish and Christian myths -- The tawdriness of the miraculous and the decline of Hell -- "The lowly stamp of their origin" : religion's corrupt beginnings -- A coda : how religions end -- Does religion make people behave better? -- There is no "Eastern" solution -- Religion as an original sin -- Is religion child abuse? -- An objection anticipated : the last-ditch "case" against secularism -- A finer tradition : the resistance of the rational -- In conclusion : the need for a new Enlightenment.
Includes bibliographical references (p. 287-294) and index.
Keywords: Religion -- Controversial literature; Rationalism